(1424) Social aspects of regional development الجوانب الاجتماعية للتنمية الإقليمية - Soliman, Azza Abdel Aziz (The Institute of National Planning, 2018)
It's an important to set out the major social issues that are likely to arise in planning for regional development. The term "Social aspects of regional development" has been understood to refer to the social relationships that develop within the regional community.